1998
DOI: 10.1055/s-2007-973570
|View full text |Cite
|
Sign up to set email alerts
|

Partial Seizures Associated with Antiphospholipid Antibodies in Childhood

Abstract: We report antiphospholipid antibody positivity in three of a consecutive series of 23 children presenting partial epileptic seizures. There was no clinical or serological evidence of systemic lupus erythematosus or other connective-tissue disease. Neither computed tomography nor magnetic resonance imaging revealed ischemic alteration. The presence of antiphospholipid antibodies in 3/23 children may indicate that immune-mediated neuronal damage could be a pathogenetic mechanism for partial epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…All types of epilepsy were seen and the seizures were generally well controlled with antiepileptic drugs. In a series of children with cryptogenic partial epilepsy 13% had high titres of antiphospholipid antibodies, all with frontal lobe seizures and normal imaging, whereas none were found in the control groups 43. One case had refractory seizures, which resolved with the temporary addition of corticosteroids.…”
Section: Antibodies Associated With Unselected Patients With Epilepsymentioning
confidence: 91%
“…All types of epilepsy were seen and the seizures were generally well controlled with antiepileptic drugs. In a series of children with cryptogenic partial epilepsy 13% had high titres of antiphospholipid antibodies, all with frontal lobe seizures and normal imaging, whereas none were found in the control groups 43. One case had refractory seizures, which resolved with the temporary addition of corticosteroids.…”
Section: Antibodies Associated With Unselected Patients With Epilepsymentioning
confidence: 91%
“…These changes have, however, been traditionally associated with either antiepileptic drug exposure (e.g., phenytoin), autoimmune diseases, or recurrent infections [4][5][6]. More recently, serum antiphospholipid antibodies have been observed in 19%-26% of adult [7][8][9] and pediatric [10][11][12] patients with both chronic epilepsy and newly diagnosed seizure disorders. Angelini et al [12] found serum antiphospholipid antibodies in 13% of patients with partial epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, serum antiphospholipid antibodies have been observed in 19%-26% of adult [7][8][9] and pediatric [10][11][12] patients with both chronic epilepsy and newly diagnosed seizure disorders. Angelini et al [12] found serum antiphospholipid antibodies in 13% of patients with partial epilepsy. Peltola et al [13] also showed glutamic acid decarboxylase (GAD) antibodies in a number of patients with refractory localization-related epilepsy, although these data have not been confirmed by other authors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another trial158 described in detail the brain injury seen in SLE patients with APS, finding frequent epilepsy (and stroke) with an increase of thrombotic and non-thrombotic brain injures. Angelini et al159 suggested that aPLs play a role in the immune-mediated pathogenic mechanism for partial epilepsy. Verrot et al160 reported that aCL was present in 20% of patients and was independent of the type of epilepsy, the antiepileptic treatment, or the age or sex of the patients.…”
Section: Aps and Vaso-ischemic (Occlusive) Diseases With Neuropsychiamentioning
confidence: 99%